2004
DOI: 10.1002/jctb.1086
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed mutations convert complexes of human recombinant T cell receptor ligands into monomers that retain biological activity

Abstract: Single-chain human recombinant T cell receptor ligands derived from the peptide binding/TCR recognition domain of human HLA-DR2b (DRA*0101/DRB1*1501) produced in Escherichia coli with and without amino-terminal extensions containing antigenic peptides have been described previously. While molecules with the native sequence retained biological activity, they formed higher order aggregates in solution. In this study, we used site-directed mutagenesis to modify the β-sheet platform of the DR2-derived RTLs, obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…These single chain rTCR ligands (RTLs) (18 -20) refold in a manner that allows binding of allele-specific epitopes (21). In this study, we present data characterizing HLA-DP-derived RTLs, including direct measurement of beryllium binding to rHLA-DP2.…”
mentioning
confidence: 99%
“…These single chain rTCR ligands (RTLs) (18 -20) refold in a manner that allows binding of allele-specific epitopes (21). In this study, we present data characterizing HLA-DP-derived RTLs, including direct measurement of beryllium binding to rHLA-DP2.…”
mentioning
confidence: 99%
“…In our previous studies, we demonstrated that both monomeric DR2-derived and I-A s -derived RTLs could protect and treat the clinical and histological signs of EAE in DR2 Tg mice (39,41) and SJL mice (40), respectively. In the current study, we used a similar approach, constructing monomeric I-A q -derived RTLs covalently linked with bCII257-270 peptide (RTL2001) (US patent no.…”
Section: Discussionmentioning
confidence: 99%
“…General methods for the design, cloning and expression of RTLs have been described previously (37,39,40). In brief, mRNA was isolated from the splenocytes of DBA1/LacJ mice using an Oligotex Direct mRNA mini kit (Qiagen).…”
Section: Rtl Construction Modification and Productionmentioning
confidence: 99%
“…Work in my laboratory has taken a reductionist approach, focused on engineering the smallest possible molecule that retains the peptide binding/TCR recognition features of the class II molecule. It appears we have achieved that goal in the form of single chain class II-derived Recombinant TCR Ligands (RTLs) consisting of the α1 and β1 domains of MHC class II molecules genetically linked into a single polypeptide chain [68][69][70][71]. The design of the RTLs was based on extensive molecular modeling studies of MHC class II proteins including crystal structures of human DR [72][73][74][75][76] and murine I-A k with covalently bound single peptides [77], and modeling studies predicted that the antigen binding domain would remain stable in the absence of the α2 and β2 Ig-fold domains [69,71,78].…”
Section: Structure Of the Mhc Class II Molecule And Design Of Rtlsmentioning
confidence: 99%
“…Along with "empty" RTLs that can be loaded exogenously with synthetic peptides, we have produced a variety of genetically-encoded variants with antigenic peptide attached by a linker to the N-terminus of the beta-chain (Table I) [64,69,79,80]. RTL molecules have been used for studying binding specificity in vitro [71,81,82], for exploring primary TCR signaling events independent of co-stimulatory input associated with the MHC II α2 and β2 domains or with other molecules expressed by antigen presenting cells [83], and for treating CD4 + T cell-mediated autoimmune disease in an MHC II/epitope-specific manner [68,70,80,83,84].…”
Section: Structure Of the Mhc Class II Molecule And Design Of Rtlsmentioning
confidence: 99%